2011
DOI: 10.1007/s00586-011-2010-4
|View full text |Cite
|
Sign up to set email alerts
|

Hemivertebra resection in children, results after single posterior approach and after combined anterior and posterior approach: a comparative study

Abstract: Purpose To compare the results after hemivertebra resection through a single posterior approach and through a combined anterior and posterior approach. Methods This is a retrospective study on patients treated by hemivertebra resection with monosegmental instrumentation for congenital scoliosis at a single institution. The patients were divided into two groups according to the surgical approach. Both groups were compared for curve correction, complication rate and perioperative data. Paired samples T test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
0
21
0
6
Order By: Relevance
“…In earlier years, hemivertebra resection by a combined anterior and posterior approach had been advocated because of its good visualization of neural structures and less technical requirement [8,9]. Later, with the wide application of the transpedicular screw, compared with the combined approach, one stage posterior approach hemivertebra resection enjoys an almost equal correction rate but with much lower surgery-related morbidity and much shorter postoperative recovery periods [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier years, hemivertebra resection by a combined anterior and posterior approach had been advocated because of its good visualization of neural structures and less technical requirement [8,9]. Later, with the wide application of the transpedicular screw, compared with the combined approach, one stage posterior approach hemivertebra resection enjoys an almost equal correction rate but with much lower surgery-related morbidity and much shorter postoperative recovery periods [9].…”
Section: Introductionmentioning
confidence: 99%
“…Later, with the wide application of the transpedicular screw, compared with the combined approach, one stage posterior approach hemivertebra resection enjoys an almost equal correction rate but with much lower surgery-related morbidity and much shorter postoperative recovery periods [9]. In recent decades, the posterior-only hemivertebra resection has gradually replaced the combined approach and became the preferred correction for this deformity [4,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Such anterior-posterior surgery fundamentally prevents the occurrence of crankshaft phenomenon, so it is widely applied in clinical practice [12][13][14]. But, its additional anterior wound brings more serious injury to patients with a high rate of postoperative complications, prolonging the operation time and length of inpatient stays, which results in greater economic burden to patients [15]. As the posterior-only approach is at risk for developing the crankshaft phenomenon, the safety of its application has been questioned by some authors.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that after an average follow-up of 4.6 years, the maintaining of correction was satisfactory in all patients, without evident The difference between preoperative and at the last follow-up crankshaft phenomenon. In 2012, a control study of Mladenov et al [15] compared the results of 12 cases receiving hemivertebra resection through a single posterior approach with 13 cases through a combined anterior and posterior approach. They found that the final therapeutic effects were almost the same.…”
Section: Discussionmentioning
confidence: 99%
“…Титановый протез, установленный вместо удаленного тела аномального позвонка, обеспечи-вал прочность, стабильность на уровне передней и средней колонн позвоночника и создавал условия для восстановления физиологического фронталь-ного и сагиттального профиля позвоночника на этом уровне. удаление тела аномального позвонка у пациен-тов старшей возрастной группы является сложным и тяжелым хирургическим вмешательством и соз-дает больший риск развития неврологических на-рушений [16][17][18]. учитывая этот факт, некоторые авторы предлагают выполнять частичную резек-цию тела аномального позвонка с выше-и нижеле-жащими межпозвонковыми дисками в сочетании со стабилизацией врожденного искривления [13].…”
Section: таблица 1/unclassified